Hasil Tindakan Percutaneous Coronary Intervention Pada Pasien Chronic Total Occlusion - Mardiyyah, Hanifah; F, Bagus Rahmat; Ummah, Difa Raisatul (ARKAVI [Arsip Kardiovaskular Indonesia), 2017)
Chronic Total Occlusion is usually found in CAD patients. Percutaneous Coronary Intervention (PCI) is good intervention in handling CTO. PCI is done in 30%  CTO patients with a success rate of 70%. Using primary case report with Descriptive cases, age 59 year with characteristics and CAD suspect. PCI was successfully done with predilatory insertion in LAD, no problems, no hemodynamic changes, no life-threatening ECG changes and no complications Keywords: Percutaneous Coronary Intervension, Chronic Total Occlusion, Left Anterior Descending